The Evaluation of Noise Exposure on Manufacturing Industry During Grinding Work Process for Palm Oil Machinery - Rosli, Khairul; Abdul Karim, Hidayah; A.Razak, Aliff Hisyam (Progress in Engineering Application and Technology, 2023)
One of the most common occupational health hazards is noise, which can cause hearing impairment, stress, and noise-induced hearing loss. Various factors that can cause hearing problems include not wearing PPE due to human behaviour factors and a lack of knowledge of the language, which can lead to miscommunication or misunderstanding. This study was conducted to identify the excessive noise in the workplace. Based on the noise risk assessment, the highest noise area in the workplace is the grinding area. So, this study will focus on reducing the excessive noise in the grinding area. The control measure chosen to reduce excessive noise is to build a soundproof room. The materials used to create this room are an exhibition booth, a wooden board, acoustic foam, fibre drums and cardboard barrels, and a welding strip curtain. The data collection will start by determining the noise level in the grinding area. The data will be collected using a sound level metre (SLM). Next, measure the noise level (neutral sound) at the project site. Its purpose was to find out whether the place was affected by noise from other work processes or not in order to get accurate data when taking noise readings. The third point is that after the process of building a soundproof room, there will be two data collection processes which are data collection before and after the installation of acoustic foam in the soundproof room. Its purpose was to find out how much noise could be reduced by using acoustic foam. In addition, it was also to find out whether the thickness of the acoustic foam also affected the rate of noise reduction. After being analysed, the data will be compared to see how much noise can be reduced by using acoustic foam material. After that, the noise reduction data will be compared with the excessive noise data in the grinding area to see how much noise was reduced after the soundproof room was installed. In conclusion, noise can be reduced by 19% by building a soundproof room in the grinding area, which can reduce the risk of being exposed to noise. The soundproof rooms can be upgraded by adding or changing better sound-absorbing materials, such as acoustic mineral wool, acoustic cotton batts, and acoustic quilted panels, depending on the suitability of the workplace.